Right Mini-thoracotomy Bentall Procedure. Issue 5 (September 2018) - Johnson, Carl A.; Siordia, Juan A.; Wood, Katherine L.; Robinson, Davida A.; Knight, Peter A.
Abstract : Objective: Bentall procedures are traditionally performed through a median sternotomy. The right mini-thoracotomy approach is increasingly used in aortic valve replacement. This approach has been shown to have decreased blood loss and hospital length of stay compared with sternotomy. A right mini-thoracotomy approach may also be beneficial in selected patients requiring aortic root surgery. We present our initial clinical experience of patients who have undergone a right mini-thoracotomy Bentall. Methods: This is a single-center retrospective review of seven patients who underwent a primary elective right anterior mini-thoracotomy Bentall. A thoracoscope was used in each case. Automated suturing technology was used for annular suturing in three of the seven patients. Clinical outcomes evaluated include 30-day mortality, intensive care and hospital length of stay, time to extubation, operative times, as well as postoperative sequelae including stroke, infection, and bleeding. Results: Median cardiopulmonary bypass, cross-clamp, and circulatory arrest time were 217, 153, and 28 minutes, respectively. Median time to extubation was 10 hours and median intensive care unit and hospital stay was 1 and 4 days, respectively. One patient had a wound infection and one returned to the operating room for bleeding. There were no in-hospital or 30-day mortalities. Conclusions: The Bentall procedure can be performed through a right anterior mini-thoracotomy in selected patients with excellent clinical results.